Effects of sponsorship in dental plans - Felipe Pinho Carneiro (2012)
The objective of this study is to identify and characterize the existence of moral hazard in the dental plans market when there is some kind of sponsorship in cash counter installments. This paper compares the behavior between plans with total sponsorship, with partial sponsorship and without sponsorship. Count Models were used to measure the over use of dental services. Empirical data from a exclusively dental plan, characterized by ANS as Odontologic Group, were collected, processed, described and analyzed to test the hypotheses raised about the moral hazard reduction when there is any kind of sponsorship. The results revealed strong evidence of regionalism in demand for appointments, showing localities where the sponsorship effect decreases the demand for appointments and other locations where the same effect increases this same demand.